Campaigns in Regional Head Elections and the Support of Kyai and Santri Pesantren in Indonesia - Aisyah Aisyah; Dewi Iriani; Martha Eri Safira; Nahrowi Nahrowi; Mohd Norhusairi bin Mat Hussin (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
This research examines the significant role of clerics (kyai) and santri in mobilizing political support during regional head elections (pilkada) and general elections in Indonesia, as well as their broader influence on local political dynamics. Based on an extensive review of literature and previous empirical studies, this research identifies that the political engagement of kyai and pesantren is largely shaped by cultural patterns embedded in practical politics, such as charismatic leadership, patron–client relationships, and communal obedience to religious figures. In addition, this study analyzes the implications of revisions to campaign regulations in pesantren following the Constitutional Court Decision Number 65/PUU-XXI/2023. This ruling permits political campaigns to take place in educational institutions and places of worship under specific legal conditions, thereby altering the normative boundaries between religious spaces and political activities. While the decision aims to ensure equality of political participation and freedom of expression, it also raises critical concerns regarding the potential politicization of religious education. By employing Al-Mawardi’s theory of political appropriateness and propriety, this research evaluates whether campaigning in pesantren aligns with the ethical foundations of Islamic political thought. According to Al-Mawardi, political actions must be guided by moral considerations and the public good (maslahah), rather than short-term political interests. The findings suggest that although campaigns in pesantren are legally permissible, they are ethically questionable. Consequently, this study argues that political campaigns in pesantren should be avoided to preserve the sanctity of religious education and to prevent the encroachment of partisan politics into educational and spiritual domains.